Female-pattern hair loss: therapeutic update - Paulo Müller Ramos; Daniel Fernandes Melo; Henrique Radwanski; Rita Fernanda Cortez de Almeida; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2023)
Abstract Female androgenetic alopecia or female-pattern hair loss (FPHL) is highly prevalent and has a great impact on the quality of life. The treatment is a routine challenge in dermatological practice, as many therapeutic options have a limited level of evidence and often do not meet patients expectations. Lack of knowledge of the pathogenesis of the hair miniaturization process and the factors that regulate follicular morphogenesis restricts the prospect of innovative therapies. There is also a lack of randomized, controlled studies with longitudinal follow-up, using objective outcomes and exploring the performance of the available treatments and their combinations. Topical minoxidil, which has been used to treat female pattern hair loss since the 1990s, is the only medication that has a high level of evidence and remains the first choice. However, about 40% of patients do not show improvement with this treatment. In this article, the authors critically discuss the main clinical and surgical therapeutic alternatives for FPHL, as well as present camouflage methods that can be used in more extensive or unresponsive cases.